High-Precision, Three-Dimensional Tracking of Mouse Whisker Movements with Optical Motion Capture Technology - Roy, Snigdha; Bryant, Jerí L.; Cao, Ying; Heck, Detlef H. (Frontiers in Behavioral Neuroscience, 2011)
The mystacial vibrissae or whiskers in rodents are sensitive tactile hairs emerging from both sides of the face. Rats and mice actively move these whiskers during exploration. The neuronal mechanisms controlling whisker movements and the sensory representation of whisker tactile information are widely studied as a model for sensorimotor processing in mammals. Studies of the natural whisker movement patterns during exploration and tactile examination are still in their early stages. Tracking the movements of whiskers is technically challenging as they move relatively fast and are very thin, particularly in mice. Existing systems detect light-beam interruptions by the whiskers or use high-speed video to track whisker movements in one or two dimensions. Here we describe a method for tracking the movements of mouse whiskers in 3 dimensions (3D) using using optical motion capture technology. Optical motion capture technology tracks the movements of small retro-reflective markers attached to whiskers of a head-fixed mouse with a spatial resolution of <0.5mm in all three dimensions and a temporal resolution of 5msec (200 fps). The system stores the 3D coordinates of the marker’s trajectories onto hard disk allowing a detailed analysis of movement trajectories bilateral coordination.